A trace element and Pb isotopic investigation into the provenance and deposition of stromatolitic carbonates, ironstones and associated shales of the ∼3.0 Ga Pongola Supergroup, Kaapvaal Craton. (1st June 2015) - Bolhar, Robert; Hofmann, Axel; Siahi, Mehrnaz; Feng, Yue-xing; Delvigne, Camille
Abstract: Major and trace element, and Pb isotopic data for chemical and clastic sedimentary rocks of the Mesoarchaean Pongola Supergroup are employed to infer aspects of the provenance and depositional environment, including ambient seawater composition. Stromatolitic carbonates of the Nsuze Group were formed in a tidal-flat setting, whereas ironstones of the Mozaan Group were deposited in an outer-shelf setting during marine transgression. Geochemical criteria, employed to test for crustal contamination and diagenetic/metamorphic overprinting, demonstrate that carbonates and ironstones preserved their primary chemical signature. In comparison to other documented Precambrian stromatolites, shale-normalised REE+Y patterns for Nsuze carbonates show pronounced enrichment in middle REE, but lack strong elemental anomalies (La, Gd, Y) that are diagnostic for derivation from open marine waters. In contrast, normalised REE+Y for ironstones exhibit distinct positive La, Gd and Y anomalies. Both rock types are devoid of normalised Ce anomalies and show only minor enrichment in Eu, suggesting deposition in anoxic environments (with respect to the Ce 3+ /Ce 4+ redox couple) accompanied by minor high-temperature hydrothermal input. Trace element geochemical data are most consistent with deposition of Nsuze carbonates in a shallow-water epicontinental basin with restricted but variable exchange to the open-ocean and dominant fluvial input, whereas ironstone precipitated in a deeper-water, epicontinental sea. Estuarine fractionation and organic complexation due to microbial activity is possibly indicated by MREE enrichment of the carbonates, also consistent with a restricted environment. Shales belonging to the Mozaan Group are characterised by high concentrations of Al and K relative to Ca, Na and Sr, indicative of pronounced in-situ weathering, coupled with K-metasomatism. The provenance is mixed, comprising (ultra)mafic and granitic source rocks. Pb isotope regression for Nsuze carbonates documents a widespread, tectono-thermal or fluid percolation event at around 2.4 Ga. Two-stage modelling of Pb isotope data, in association with published Sr and Nd isotope data, requires a source for Nzuse carbonates that was derived from evolved continental crust with an elevated U/Pb ratio (μ-value) and an approximate crustal residence time of ∼100–600 Ma.